DEVELOPMENT OF PERSONAL NUTRITION APPLICATIONS FOR PATIENTS WITH DIABETES MELLITUS TYPE 2 - Adi Chandra, Joshua
Type 2 diabetes mellitus is a type of diabetes mellitus which is characterized by high blood sugar levels above normal limits and is caused by insulin resistance in the body. The percentage of people with type 2 diabetes is also the highest of all types of diabetes mellitus, around 90 to 95% based on data from centers for disease control and prevention. If not treated properly, this disease can lead to advanced diseases such as heart disease, neuropathy, and kidney damage. Then to deal with it, required treatment with medication and lifestyle changes. One lifestyle that needs to be considered is nutrition and the type of food eaten. People with type 2 diabetes are advised to avoid foods with high sugar and fat content, then high-fiber foods are also needed. To maintain nutritional intake in patients, an application on a smartphone can be used. Currently there are many applications to maintain nutrition for diabetics, but there are still shortcomings in the form of application suggestions that are not in accordance with the advice of medical personnel, the price of using the application is expensive, and users do not understand the suggestions from the application. Therefore, in this study, to overcome the problem of nutritional advice, the application developed was made with communication features between doctors and patients and nutritional analysis features based on suggestions from the Indonesian endocrinology association. In ensuring the results of the development, testing was carried out using the net promoter score method and the app quality evaluation method. The data from the test results of application development using the net promoter score method yielded a value of 64.7% and the results of the app quality evaluation method succeeded in obtaining a value of 8,624 for conformity with medical conditions. From these results, it is found that the way to solve the problem is correct and the method used can help increase user confidence in using the application